Study of the effect of the introduction of plant fibers on the properties of composites - DAIRI, Badrina (Biopolymer Applications Journal, 2025)
To reduce the massive consumption of HDPE, which causes environmental problems, we offer biodegradable composite materials, at low cost and with low density. In this context, a study devoted to the valorization of lignocellulosic waste, a particular interest has been brought to the pistachio shell filler, as vegetable filler in the manufacture of high-density polyethylene matrix composite materials with a filler rate of 5% to 15%. The HDPE/FCP composites were initially mixed in a calendar before preparing the different sample shapes with a thickness of 2 and 3mm by compression at 190°C. The latter were characterized by various techniques: rheological, mechanical, physical tests, and morphological.